PENGARUH CACING TANAH Lumbricus rubellus TERHADAP LAJU VERMIKOMPOSTING SAMPAH PERKOTAAN - Romi Abdullah Panatagama; Moch. Arifin; Supamrih Supamrih (UPN VETERAN JAWA TIMUR, 2018)
The purpose of this research is to know the effect of earthworm Lumbricus rubellus on vermicomposting rate of urban waste. The research was conducted from October to December 2016. The research was conducted in the laboratory of Land Resources of the Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran’’ Jawa Timur. The method used in this study was the randomized compartment design which is arranged in completely random. The design of the distributed plot is comparing from two experimental unit types between the main plot and the plot subgroup where the environmental design for both can be the same or different. Treatment on main plot (PU) in the form of composting using earthworm (V) with 2 levels of V0 without worms and worms using V1. While in the treatment of child plot (PA) in the form of composting time (M) with 5 levels namely; M1 = Week 1, M2 = Week 2, M3 = Week 3, M4 = Week 4, and M5 = Week 5. The result of vermicomposting rate influenced by earthworm Lumbricus rubellus obtained total N, total P, total K, C/N ratio was good. Composting using earthworms gives significantly different results than regular composting. The value of observation parameters of composting using earthworms was not significantly different with increasing time.